Design and experiment of nail tooth picking up device for strip type residual film recycling and baling machine - Jiang, Deli; Yan, Limin; Chen, Xuegeng; Mo, Yisong; Yang, Jiacheng (International Journal of Agricultural and Biological Engineering, 2024)
In order to solve the problem of residual film pollution caused by large area of cotton mulched planting in Xinjiang, a strip type residual film recycling and baling machine was designed, which can complete mulching film picking up, impurities separation, baling and other operations. The picking up device, as the key part of residual film recycling machine, was designed and analyzed. The kinematics of the pick-up nail tooth was analyzed, and its motion equation, motion trajectory and the conditions for completing the film pick-up were determined. And the key parameters were determined by analyzing the conditions of no missing picking and the stress of the residual film. According to the Box-Benhnken test design principle, field experiments were carried out with the forward speed of machine, the pickup speed ratio and the number of auxiliary film removing mechanisms as the key experimental factors, and the residual film pickup rate, the cotton stalk content and the residual film winding rate as the operation performance indexes of the picking up device. The mathematical models between the experimental factors and indexes were established, and the effect of each factor was analyzed. Through multi-objective parameter optimization and field experiment, the optimal combination of operation parameters was obtained as follows: the forward speed of machine of 1.67 m/s, the pickup speed ratio of 1.13, and the number of auxiliary film removing mechanisms of 6. Under this parameter combination, the pickup rate of residual film was 88.9%, the cotton stalk content in recycled residual film of 3.9%, and the residual film winding rate of 1.5%. The absolute error with the theoretical value was less than 0.6%. The research results show that the picking up device has stable operation performance and good residual film recycling effect, which meets the design and practical operation requirements.Keywords: strip mulching film, recycle, pick-up nail tooth, motion analysis, parameter optimization, film removing mechanismDOI: 10.25165/j.ijabe.20231606.7563Citation: Jiang D L, Yan L M, Chen X G, Mo Y S, Yang J C. Design and experiment of nail tooth picking up device for strip type residual film recycling and baling machine. Int J Agric & Biol Eng, 2023; 16(6): 85–97.